Designing Deep Learning-Oriented Biology Learning Devices in a Curriculum Review Course: a Conceptual Study for Undergraduate Pre-Service Teachers - Rikardus Herak (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This conceptual study develops a framework for designing deep learning-oriented biology learning devices in an undergraduate Curriculum Review course. The problem addressed is that pre-service teachers often prepare ATP, teaching modules, student worksheets, and assessment instruments as administrative documents rather than as an integrated design system for meaningful biology learning. The study used a literature-based conceptual synthesis by reviewing recent sources from 2016 onward related to deep learning, science learning, formative assessment, pre-service biology teacher competence, misconception diagnosis, and curriculum design. The synthesis produced a six-stage design framework: diagnosing learner characteristics and misconceptions, mapping essential biological concepts, selecting authentic phenomena, designing inquiry-based learning sequences, aligning formative and summative assessment, and preparing reflection-based revision. The framework positions ATP as the direction of learning, the teaching module as the learning route, LKPD as a thinking scaffold, and assessment as evidence of conceptual understanding and transferable competence. The article also proposes a practical rubric for evaluating student-produced learning devices through six dimensions: alignment, conceptual accuracy, inquiry depth, contextual relevance, assessment validity, and feasibility. The findings indicate that deep learning in biology should not be limited to an attractive label in the module; it must be visible in learning objectives, student inquiry tasks, questions, assessment criteria, feedback, and reflection. The study concludes that Curriculum Review courses can become stronger professional learning spaces when lecturers evaluate both administrative completeness and pedagogical quality. The framework is recommended for use in peer review, microteaching, lesson study, and school-based practicum before empirical validation in future research.